REFLECTIVE TEACHING ON THE USING OF CONTEXTUAL TEACHING AND LEARNING NOTION: CASE IN SECONDARY SCHOOL - Nasrullah Nasrullah; Elsa Rosalina (Politeknik Negeri Bengkalis, 2019)
The success of teaching needs to consider what strategy should be used to identify an effective way for students to absorb the material. These could be the main priority in the teaching process done by teachers involving teaching English to review their failure in the past, which tend to emphasize the role of a teacher in teaching and learning process what so-called teacher-centered. In the next phase to provide alternative solution, there is a contextual teaching and learning as an approach which adopts various strategies and makes students have an opportunity to be more explorative and thoughtful to learn in class as well as put them as the actor in learning milieus as it is called as student-centered helps teacher to reflect the teaching process whilst connecting academic material to the learners’ context in their daily lives in terms of personal and social contexts for promoting learning motivation.This was descriptive research that described to which extent of the implementation of contextual teaching and learning in the teaching and learning English in SMAN 1 Banjarmasin. There was one English teacher to be observed as a subject of research and involving 63 students in the process of English teaching in the classroom of the second and third grade of SMAN 1 Banjarmasin. To get the data, the researcher used observation and interview.The research found that the teacher employed several principles of contextual teaching and learning involving constructivism, questioning, inquiry, learning community, and authentic assessment in the classroom activities conducted by the observed teacher.Keywords: Contextual Teaching and Learning, Teaching Approach, Reflective Teaching